RELEVANSI SPIRITUALITAS KETUJUH JEMAAT DI KITAB WAHYU PADA JEMAAT KRISTEN DI GBT KAO NGALIYAN SEMARANG - Saputra, Rudyanto Chandra (Sekolah Tinggi Teologi Kristus Alfa Omega, 2018)
The most sought spiritual attitude when he comes the second time, is loyalty, Loyalty to Faith is believed, which is demonstrated by continuing enthusiasm in serving His work on this earth. The fact that the church, the church of God, began to look weak in service, worship and other spiritual activities. The purpose of this study was to describe the relevance or similarity between the spirituality of the seven churches in the book of Revelation, which greatly degenerated its spirituality compare with the conggregation at the GBT KAO Ngaliyan Semarang. The results of hypothesis testing calculations, is that the comparison of µ0 values is 40% or equal to 72, while the mean empirical score is 147.8. Thus it is known that the hypothesis value (µ0) or equal to 32, is not the same as the empirical score value of 33.475. Or with other meanings the empirical score value is proven to be greater than the hypothesis value (µ0). The 7th Spirituality Relevance Hypothesis in the book of Revelation to the conggregation of GBT KAO Ngaliyan is greater than or equal to (≥) 40% of the maximum value received and the 7th Relevance of the Spirituality of the Church with the GBT KAO Ngaliyan congregation is less or not the same as (<) 40% of the maximum value is rejected. Based on the calculation of the total score obtained the percentage value of spirituality relevance is 42% So, it can be said to be quite understanding. So, the spirituality of the seven churches in Revelation chapters 2 and 3 is not relevant to the spiritual attitudes of the GBT KAO Ngaliyan congregation in Semarang